2006
DOI: 10.1002/ange.200602221
|View full text |Cite
|
Sign up to set email alerts
|

A Chiral Primary Amine Thiourea Catalyst for the Highly Enantioselective Direct Conjugate Addition of α,α‐Disubstituted Aldehydes to Nitroalkenes

Abstract: General Information: All reactions were performed under a nitrogen atmosphere in oven-dried round-bottomed flasks fitted with rubber septa or yellow polyethylene stoppers. Liquid reagents were transferred with stainless steel syringes. Flash Chromatography was performed with EM Science silica gel 60 (230-400 mesh). Materials:Dichloromethane was distilled from CaH 2 at 760 Torr. Commercially available aldehydes were purified by distillation from anhydrous calcium sulfate and/or column chromatography prior to us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0
3

Year Published

2007
2007
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(32 citation statements)
references
References 94 publications
1
28
0
3
Order By: Relevance
“…[9] Jacobsen and co-workers further explored a primary amine-thiourea catalyst 4 to catalyze the addition of a,a-disubstituted aldehydes to nitroolefins using only a two-fold excess of aldehyde. [10] Wennemers et al designed tripeptides 5, which was among the most efficient asymmetric catalysts for conjugate addition reaction to date.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Jacobsen and co-workers further explored a primary amine-thiourea catalyst 4 to catalyze the addition of a,a-disubstituted aldehydes to nitroolefins using only a two-fold excess of aldehyde. [10] Wennemers et al designed tripeptides 5, which was among the most efficient asymmetric catalysts for conjugate addition reaction to date.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, whereas there are several examples of primary amine catalyzed Michael reaction of aldehydes and nitroolefins, most of them used a,a-disubstituted aldehydes as donors. [12] To explore the potential application of these principles to the anti-Michael reaction we chose (tert-butyldimethylsilyloxy)acetaldehyde (1) as a donor, and examined the Michael reaction using b-nitrostyrene (2) as a model acceptor (Table 1). Hydroxyacetaldehyde protected with tert-butyldimethylsilyl (TBS) was chosen based on our successful use of TBS-protected dihydroxyacetone in anti-Mannich and synaldol reactions.…”
mentioning
confidence: 99%
“…N-Alkyl ethyl ketones afforded Michael adducts with complete regioselectivity, high enantiomeric excesses (up to 99 % ee), and diastereoselectivity favoring the anti isomers (up to 20:1 dr). Jacobsen and co-workers [51] have also shown that a similar chiral primary amine/thiourea catalyst is highly effec- Scheme 28. tive in the addition of α,α-disubstituted aldehydes to nitro alkenes, generating synthetically versatile nitro aldehyde adducts. Simultaneous activation of both nucleophile and electrophile allows this challenging transformation to take place under mild reaction conditions and with broad substrate scope (Scheme 28).…”
Section: Direct Michael Additions Of Unmodified Aldehydes and Ketonesmentioning
confidence: 99%